Fenomena Penggunaan Cadar di Kalangan Pemudi Muslimah Banjarmasin: Identitas Sosial di Tengah Arus Tren Mode Berpakaian - Abdillah, Muhammad Torieq; Rahmattika, Nadia (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
The phenomenon of using the veil among Muslim youth Banjarmasin has pretty much been found since 2016. This study aims to determine the reasons and motivations, as well as the meaning of hijrah and fashion trends in dress, to participate in affecting young Muslim Banjarmasin in using the veil. The research method used is descriptive qualitative with field studies. The results of this study indicate that the reasons and motivations are based on a strong desire from oneself and the influence of a supportive environment and also because there is a figure who is used as a role model. Then, there are different meanings in mentioning whether to use the veil can be said to emigrate with opinions that are equally strong between mentioning part of the hijrah and not. Finally, wearing a face veil is not a fashion trend because wearing a face veil is part of the shari’a, as the opinion of the Shafi’i school.